Analyzing the dual space of the saturated ideal of a regular set and the local multiplicities of its zeros. (19th May 2022) - Li, Xiaoliang; Niu, Wei
Abstract : In this paper, a method is proposed to analyze the structure of dual space of the saturated ideal generated by a regular set and the local multiplicities of its zeros. In detail, we generalize the squarefree decomposition of univariate polynomials to the so‐called pseudo squarefree decomposition of multivariate polynomials and then propose an algorithm for decomposing a regular set into a finite number of simple sets. From the output of this algorithm, the multiplicities of zeros could be directly read out, and the real solution isolation with multiplicity can also be easily produced.